Association between asthma and sugar-sweetened beverage consumption in the United States pediatric population. (4th May 2022) - Xie, Luyu; Atem, Folefac; Gelfand, Andrew; Delclos, George; Messiah, Sarah E.
Abstract: Objectives: United States (US) youth consume an average of 10 teaspoons of added sugar from sugar-sweetened beverages (SSB) on any given day. Few population-based studies have examined the association between SSB consumption and asthma in children and adolescents. This study aimed to examine the association between SSB consumption and asthma in the US pediatric population. Design: Analytical cross-sectional study. Setting and Participants: A total of 9, 938 children aged 2-to-17 years old who participated in the 2011-2016 National Health and Nutrition Examination Surveys. SSB consumption was categorized into 3 groups based on the caloric intake from 24-hour food recall data as follows: 1) no consumption (0 kcal/day); 2) moderate consumption (1-499 kcal/day); and 3) heavy consumption (≥ 500 kcal/day). The primary outcome of interest was self-reported current asthma condition. Results: Asthma prevalence estimates were significantly higher in heavy (16.4%) and moderate (11.0%) SSB consumers versus non-consumers (7.5%) ( p < 0.05 for both comparisons). The adjusted odds of asthma were twice that among children with heavy SSB consumption (aOR 2.01, 95% confidence interval [CI] 1.31-3.08) versus non-SSB consumers. The odds of asthma were higher among those who consumed fruit drinks (aOR 2.51, 95% CI 1.55-4.08), non-diet soft drinks (aOR 1.89, 95% CI 1.23-2.89) and sweet tea (aOR 1.87, 95% CI 1.13-3.09) compared to nondrinkers. The effect was independent of obesity status ( p -interaction = 0.439). Conclusions: Findings here suggest a dose-response relationship between SSB intake and asthma diagnosis, therefore controlling SSB consumption may potentially improve pulmonary health risk in the US pediatric population.